Understanding Navajo K–12 Public School Finance in Arizona through Tribal Critical Theory. Issue 5 (May 2019) - Martinez, David G.; Jiménez-Castellanos, Oscar; Begay, Victor H.
Background/Context: Currently, Native American education policy reports and empirical research papers have largely focused on sociocultural challenges to Native sovereignty and the policy that impedes Native sovereign states. This paper deviates from that theme by implicating policy as preventing improvement of educational outcomes by proxy of the fiscal revenue available to reservation schools, focusing specifically on the Navajo Nation. To date, this is the first empirically driven, Native-specific school finance study that attempts to compare how Anglo and Native schools are funded and how the quality and dispersion of this funding affects Native education and outcomes. Purpose/Objective/Research Question/Focus of Study: This study reports on a longitudinal descriptive analysis of school fiscal revenue (2006–2012), comparing Navajo K–12 school districts against Arizona public school districts. This empirical research paper attempts to answer the following questions: How did Navajo K–12 public school district demographics compare to those of Arizona public school districts from 2006 to 2012? How did Navajo K–12 public school districts perform academically compared to Arizona public school districts from 2006 to 2012? How did Navajo public school district tax rates and assessed property valuation compare to those of Arizona public school districts from 2006 to 2012? How did Navajo public school district revenues compare to those of Arizona public school districts from 2006 to 2012? Research Design: This research study is a univariate statistical analysis (i.e., mean, median, standard deviation, range, and percentile) examining general descriptions of individual fiscal revenue variables for schooling. Data Collection and Analysis: The data comprised publicly available Arizona Department of Education Excel files (Excel v14.0) merged into one consolidated dataset imported to SPSSv22.0. Our analysis began by selecting Navajo public school districts from our dataset and then comparing them to Arizona public districts (excluding Navajo and nontraditional LEA districts) from 2006 to 2012. Findings/Results: This study has two conclusions: (a) There is a clear and growing achievement gap between Navajo and Arizona districts; and (b) Our results seem to suggest that Arizona's equalization formula is not effectively counterbalancing the impact of local property wealth, as shown by the disparities in combined state and local revenue between Navajo K–12 school districts and Arizona districts. Conclusions/Recommendations: The findings in this study indicate that Arizona must address policy and practice in order to remedy the educational disparity between Navajo students and their non-Navajo peers. Navajo Nation schools require agency to designate priorities and state funding to meet these priorities.